DISSIPASI β-SIFLUTRIN PADA LAHAN KANGKUNG (Ipomoea reptans) - Ismarti Ismarti (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2017)
b-cyfluthrin has been in agricultural use in the recent years for controlling Lepidopteran pest affecting leafy vegetables crops. The extensive use of synthetic pyrethroids like b-cyfluthrin has resulted in wide spread environmental contamination. A study on residue dynamic of b-cyfluthrin applied to kangkong-land has been conducted. Buldock 25 EC with maximum recommended dose was used. The analysis was performed on kangkong land while land without kangkong used as control. Extraction was carried out with the soxhlet method, while the cleaning up process was carried out with carbon-and-florisil-double-layered column. High resolution gas chromatography with Electron Capture Detector (ECD) was used to determine the concentration. On kangkong-land with 14,52% organic matter, sorption of b-cyfluthrin was observed. Residue of b-cyfluhtrin on soil increased to 16th days. The dissipation rate on land without kangkong and kangkong-land are fast with dissipation rate 2,5 x 10-1 day-1 and 5,76 x10-1 day-1respectively. Organic matter play an important role in the dissipation rate of b-cyfluthrin residue in the tropical farmland of Indonesia.